Influence of muscle‐belly and tendon gearing on the energy cost of human walking. (14th February 2022) - Monte, Andrea; Tecchio, Paolo; Nardello, Francesca; Bachero‐Mena, Beatriz; Ardigò, Luca Paolo; Zamparo, Paola
Abstract : This study combines metabolic and kinematic measurements at the whole‐body level, with EMG and ultrasound measurements to investigate the influence of muscle‐tendon mechanical behavior on the energy cost (Cnet ) of walking (from 2 to 8 km·h −1 ). Belly gearing (Gb = Δmuscle‐belly length/Δfascicles length) and tendon gearing (Gt = ∆muscle‐tendon unit length/∆muscle‐belly length) of vastus lateralis (VL) and gastrocnemius medialis (GM) were calculated based on ultrasound data. Pendular energy recovery (%R) was calculated based on kinematic data, whereas the cumulative activity per distance travelled (CMAPD) was calculated for the VL, GM, tibialis anterior, and biceps femoris as the ratio between their EMG activity and walking speed. Finally, total CAMPD (CMAPDTOT ) was calculated as the sum of the CMAPD of all the investigate muscles. Cnet and CMAPDTOT showed a U‐shaped behavior with a minimum at 4.2 and 4.1 km·h −1, respectively; while %R, VL, and GM belly gearing showed an opposite trend, reaching a maximum (60% ± 5%, 1.1 ± 0.1 and 1.5 ± 0.1, respectively), between 4.7 and 5 km·h −1 . Gt was unaffected by speed in GM (3.5 ± 0.1) and decreased as a function of it in VL. A multiple stepwise linear regression indicated that %R has the greatest influence on Cnet, followed by CMAPDTOT and GM belly gearing. The role of Gb on Cnet could be attributed to its role in determining muscle work: when Gb increases, fascicles shortening decreases compared with that of the muscle‐belly, thereby reducing the energy cost of contraction.